EUS-guided cholecystoduodenostomy for acute cholecystitis with an anti-stent migration and anti-food impaction system; a pilot study. (January 2016) - Takagi, Wataru; Ogura, Takeshi; Sano, Tatsushi; Onda, Saori; Okuda, Atsushi; Masuda, Daisuke; Imoto, Akira; Takeuchi, Toshihisa; Fukunishi, Shinya; Higuchi, Kazuhide
Background: Recently, endoscopic ultrasound-guided gall bladder drainage (EUS-GBD) has been reported using a self-expandable metallic stent. To prevent stent migration and food flowing into the common bile duct through the cystic duct, we perform a novel EUS-guided cholecystoduodenostomy. The aim of our study was to evaluate the safety and feasibility of EUS-guided cholecystoduodenostomy with an anti-stent migration and anti-food impaction system. Methods: A total of 16 consecutive patients who underwent EUS-guided cholecystoduodenostomy for acute cholecystitis were included in this study. Results: Technical and clinical success was obtained in all patients. The median procedure time was 26.9 min (range 19–42 min). Median follow-up time was 181.5 days (range 18–604 days), and in this time, recurrence of acute cholecystitis was not seen in all patients. Adverse events such as stent migration and cholangitis were not seen in any patients, although pneumoperitoneum was seen in one patient. Conclusion: Our technique may be favorable and effective for the prevention of adverse events on EUS-GBD.